The Effect of Integrative Biopsychosocial Therapy on Comorbid Major Depressive Disorder and Posttraumatic Stress Disorder - Ortibano, Mark T.; Madrigal, Dennis; Singson, Deborah Natalia (Technium Social Sciences Journal, 2024)
Comorbid Major Depressive Disorder (MDD) and Posttraumatic Stress Disorder (PTSD) pose significant clinical challenges due to their complex and intertwined symptoms. This study examined the effectiveness of integrative biopsychosocial therapy in treating these conditions in a female participant, aiming to improve anxiety, depression, sleep disturbance, and overall psychological well-being. Using an experimental approach, an ABA single-subject reversal design was employed. The participant received tailored integrative biopsychosocial therapy and data were analyzed visually. Initially symptomatic of MDD and PTSD, the participant showed improvements in mood regulation, relational indicators, and cognitive functioning during the intervention. Quantitative data indicated substantial reductions in anxiety, depression, and sleep disturbance, confirming the therapy's effectiveness. However, PTSD symptoms showed variability, indicating the need for ongoing support. The study highlights the safety and effectiveness of integrative biopsychosocial therapy in enhancing mood, relational stability, and cognitive function in individuals with comorbid depression and PTSD. Future research should address sample diversity, extend baseline periods, and tailor PTSD interventions to optimize outcomes and expand evidence-based practices. Limitations include the small sample size and the need for longer-term follow-up to assess sustained effects. The intricacy of treating trauma and the variability in PTSD symptoms require further investigation. This study informs clinicians and researchers about the effectiveness of integrative biopsychosocial therapy, emphasizing the importance of addressing biological and psychosocial factors in treatment planning for comorbid depression and PTSD.